The effect of increasing CO2 concentrations on its capture, biomass production and wastewater bioremediation by microalgae and cyanobacteria - Ana L. Gonçalves (2016)
The accumulation of carbon dioxide (CO2) in the atmosphere, as well as the enrichment of water courses in nutrients are environmental issues associated to numerous impacts on ecosystems. Several attempts have been made to address these issues, but the cost and sustainability of current methodologies are still a concern. Cultivation of photosynthetic microorganisms appears as a sustainable solution because: (i) they can effectively uptake CO2 and nutrients, such as nitrogen and phosphorus; and (ii) the resulting biomass can be processed into valuable products. In this study, the effect of different CO2 concentrations (from approximately 0.04 to 10% v/v) on CO2 capture, biomass production and nutrients (nitrogen and phosphorus) uptake was assessed for the microalgae Chlorella vulgaris and Pseudokirchneriella subcapitata and the cyanobacteria Synechocystis salina and Microcystis aeruginosa grown at laboratory scale under batch mode. For the studied range of CO2 concentrations, C. vulgaris, S. salina and M. aeruginosa have reached the highest biomass productivities (0.126 +/- 0.033 g(dw) L-1 d(-1)) and carbon fixation rates (0.101 +/- 0.027 g(C) L-1 d(-1)). These microorganisms have also been effective in nutrients uptake, reaching removal efficiencies close to 100%. Through mathematical modelling, it was possible to conclude that optimal CO2 concentration for these microorganisms was 5.35 +/- 0.34% (v/v).